THE LINK BETWEEN VLS AND READING COMPREHENSION - Darmawan Budiyanto; Gaya Tridinanti; Rahma Dianti; Muhammad Rasyid Ridho (Universitas Indo Global Mandiri, 2022)
The purpose of this study was to determine the correlation between vocabulary learning strategies and reading comprehension, as well as the extent to which vocabulary learning strategies contributed to students' reading comprehension. The correlational research design was used for this study. The sample of 68 students was chosen using the purposive sample technique. The questionnaire on vocabulary learning strategies and the reading comprehension test were used to collect data and Pearson Product Moment and regression analysis were used to analyze the obtained data. The study found that students' vocabulary learning strategies questionnaire and reading comprehension test scores were in the average range. First, with a p-value 0.003 less than the alpha value of 0.05, there was a significant correlation between vocabulary learning strategies and reading comprehension of tenth-grade students at SMA N 10 Palembang. The R-value of.358 indicates that Ha was accepted and Ho (null hypothesis) was automatically rejected. A low correlation was discovered between vocabulary learning strategies and reading comprehension of SMA N 10 Palembang tenth-grade students. Second, the regression value revealed 0.128 influences of vocabulary learning strategy and reading comprehension, implying that the contribution and interaction effect of vocabulary learning strategy and reading comprehension was 12.8%.